Spinoza's - Garver, Eugene (Philosophy & theology, 2012)
The Preface to Part 4 of Spinoza’s Ethics claims that we all desire to formulate a model of human nature. I show how that model serves the same function in ethics as the creed or articles of faith do in the Tractatus Theologico-Politicus, the function of allowing the imagination to provide a simularcrrum of rationality for finite, practical human beings.